The Meaning Of Khatmil Qur'an In Prayer As A Graduation Requirement For Students Of Wali Songo Situbondo Islamic Boarding School - rohmah, umi nuriyatur (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2025)
This research describes the practice of reciting the Qur'an in the tradition of khatmil Qur'an at the Wali Songo Situbondo Islamic Boarding School. The focus of the study in this research is to find out the practice and meaning of the actors of the khatmil Qur'an tradition in prayer at the Wali Songo Situbondo Islamic Boarding School. This field research uses a qualitative approach. Data collection is done through observation interviews, and documentation. Observations were conducted for two months at the Wali Songo Situbondo Islamic Boarding School, namely from September to October 2023 and interviews with several informants who were directly involved in the implementation of khatmil qur'an while documentation was used to collect data related to the research theme. Karl Mannheim's sociology of knowledge theory was used to analyze the meaning of the actors in this practice. This study concluded two things; first, the practice of khatmil Qur'an in prayer is a test for tafidz students who have memorized 30 juz as a requirement for graduation of the Qur'an. In its implementation, the khatmil Qur'an activity in prayer is carried out overnight, namely after the isya' prayer until dawn. Second, the meaning of the practice of khatmil Qur'an in prayer based on Karl Mannheim's theory, three categories of meaning are found, namely, objective meaning as a series of bil hifdzi Qur'an recitation activities carried out by tahfidz students as a graduation requirement. Expressive meaning as ittiba' to the habits carried out by Usman bin Affan, strengthening memorization, and testing the students' memorization. While the documentary meaning is the practice of cultivating the recitation of the Qur'an in everyday life.